Option of intercropping for irrigated coffee with corn and beans in the semiarid region of Minas Gerais, Brazil - Silva, Vânia; Pasqualotto, Allan Teixeira; Andrade, Fabrício Teixeira; Lima, Luiz Antonio; Carvalho, Gladyston Rodrigues; Rezende, Ramiro Machado (Coffee Science - ISSN 1984-3909, 2016)
The objective was to appoint an intercropping option for the cultivation of sprinkler irrigated coffee crops with corn and beans. During the first three semesters after its planting, the cropping coffee was carried out with different intercropping systems: two corn crops planted in 3 rows and one crop of 4 rows of dry beans; one crop of corn in 3 rows followed by one crop of dry beans in 6 rows and one crop of corn in 3 rows together with 2 rows of beans; two crops of corn planted in 2 rows only; 2 crops of 4 rows of beans; 2 crops of 6 lines of dry beans; coffee only. Randomized blocks with four replicates was used. Coffee yield without corn or beans was 47 bags of 60 kg ha-1. The intercropped systems that used three lines of maize resulted in high corn yield of 13.73 Mg.ha-1 but it was harmful to growth and coffee yield; the system that used two lines of maize produced 8.36 Mg.ha-1 of corn and 32 bags of coffee per hectare. The intercropped system with 2 crops of 4 rows of beans; 2 crops of 6 lines of dry beans didn´t affect coffee development and yield and produced 1.72 and 2.21 Mg.ha-1 of beans. The intercrops had positive economic return. The intercropped system with two crops of six lines of beans is the technical and economical option suitable for the formation of sprinkler irrigated coffee crop in the semiarid region of Minas Gerais, Brazil.